2005
DOI: 10.2106/jbjs.d.02342
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Painful Pseudoparesis Due to Irreparable Rotator Cuff Dysfunction with the Delta III Reverse-Ball-and-Socket Total Shoulder Prosthesis

Abstract: Total shoulder arthroplasty with the Delta III prosthesis is a salvage procedure for severe shoulder dysfunction caused by an irreparable rotator cuff tear associated with other glenohumeral lesions. Complications were frequent following both primary and revision procedures, but they rarely affected the final outcome. The procedure has a substantial potential to improve the condition of patients with severe shoulder dysfunction, at least in the short term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
421
4
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 621 publications
(458 citation statements)
references
References 36 publications
24
421
4
9
Order By: Relevance
“…On the other hand, our in vitro results may confirm clinical studies that rarely observed glenoid loosening in the initial postoperative period (Boileau et al, 2006, Werner et al, 2005. This would suggest that in vivo loosening of the reverse glenoid component may not be due to poor primary stability but could be attributed to other factors such as poor secondary stability due to inadequate bone quality, insufficient screw purchase or component malpositioning (Guery et al, 2006, Werner et al, 2005. If these are the failure modes, appropriate in vitro biomechanical test standards should be developed to address these particular clinical problems.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…On the other hand, our in vitro results may confirm clinical studies that rarely observed glenoid loosening in the initial postoperative period (Boileau et al, 2006, Werner et al, 2005. This would suggest that in vivo loosening of the reverse glenoid component may not be due to poor primary stability but could be attributed to other factors such as poor secondary stability due to inadequate bone quality, insufficient screw purchase or component malpositioning (Guery et al, 2006, Werner et al, 2005. If these are the failure modes, appropriate in vitro biomechanical test standards should be developed to address these particular clinical problems.…”
Section: Discussionsupporting
confidence: 85%
“…The lack of micromotion in the reverse shoulder implants we observed may be due to less aggressive biomechanical loading or more robust fixation than has been reported for conventional total shoulder arthroplasty (Anglin et al, 2000a, Collins et al, 1992. On the other hand, our in vitro results may confirm clinical studies that rarely observed glenoid loosening in the initial postoperative period (Boileau et al, 2006, Werner et al, 2005. This would suggest that in vivo loosening of the reverse glenoid component may not be due to poor primary stability but could be attributed to other factors such as poor secondary stability due to inadequate bone quality, insufficient screw purchase or component malpositioning (Guery et al, 2006, Werner et al, 2005.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These indications and contraindications continue to be debated, such as how one defines pseudoparalysis and at what age a patient is ''too young'' for a reverse shoulder arthroplasty. The improved outcomes possible with this prosthesis have been well documented [18,45,47,48]. The improvements in pain and ROM have therefore made reverse arthroplasty an increasingly commonly selected option for patients and subject for study.…”
Section: Discussionmentioning
confidence: 99%
“…The variables in the current prostheses have been developed to address concerns that have arisen with reverse shoulder arthroplasty. The persistent problems and high complication rate with this procedure have been described extensively in the current literature, with complications including hematoma formation [48], infection [5,15,18,45,48,49], scapular notching [28,44,45,49], instability [18,48,49], acromial insufficiency [15,48], and glenoid component failures [14,17,42,45]. Additionally, complications and patient satisfaction vary among primary cuff tear arthroplasty, revision cases, and fractures [5,15,18,45,48,49].…”
Section: Discussionmentioning
confidence: 99%